A review and analysis of the components of potentially effective perinatal mental health interventions for infant development and mother-infant relationship outcomes. (7th February 2022) - Newton, Katherine; Taylor Buck, Elizabeth; Weich, Scott; Uttley, Lesley
Abstract: Children of mothers with serious mental health difficulties are at increased risk of developing mental health difficulties themselves in their own lifetime. Specialist interventions delivered in perinatal mental health services offer an opportunity to support the infant's development and long-term mental health. This review aimed to systematically evaluate the shared elements of successful perinatal mental health interventions that underpin improved outcomes for infants whose mothers experience perinatal mental health difficulties. Nine electronic databases were searched comprehensively for relevant controlled studies of perinatal mental health interventions, and a narrative synthesis undertaken to assess whether statistically significant benefits were noted. Sixteen studies, trialing 19 interventions, were analyzed using a narrative approach and grouped according to reported effectiveness. Eight interventions demonstrated significant improvements in infant outcomes and/or mother–infant relationship outcomes and were used to inform the analysis of the included interventions' components. While the interventions identified were diverse, there were common components which potentially underpin successful interventions for infants whose mothers are experiencing mental health difficulties, including: facilitation of positive Mother×Infant interactions; helping mothers to understand their infant's perspective or inner world; and the use of video feedback.